STRATEGI PEMULIAAN JAMBU METE SPESIFIK LOKASI MELALUI METODE OBSERVASI - Edi Wardiana; Budi Martono; Dani . (Jurnal Tanaman Industri dan Penyegar, 2011)
Cashew is a perennial plant so that its breeding cycle requires a relatively long time. One alternative that can be done to accelerate the investigation of superior varieties is the observation method on the existing populations which have expressed their potential genetics and has a preference for the local farmers community. The observation method are directed to investigate the superior varieties for specific location where the selection process involving the local farmers community. This method are identical to the model of Participatory Plant Breeding (PTP) that are oriented to the multilevel user needs (industrial and end user). In order to increase the efficiency and effectivity of the observation methods are recommended  : (1) to increase the empowerment of local farmers communities, (2) to provide the adequate confidence from the government and or plant breeders to the farmers beginning from planning stage until characters selection stage, and (3) to add the location of BPT with their distribution in more specific location based on differences in the biophysical environment, agronomic and socio-economic of local farmers community.